DETERMINANTS OF AUDIT DELAY ON MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2015-2020 PERIOD - Yunika Prastiyani Winda Ningrum; Ceacilia Srimindarti (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2022)
This study aims to examine and analyze the effect of firm size, profitability, solvency, and the size of the public accounting firm on audit delay in mining companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The sampling method used is purposive sampling and obtained as many as 55 samples. The analytical method used in this research is multiple linear regression analysis. The results of this study indicate that firm size has a positive effect on audit delay, profitability and solvency have no effect on audit delay. While public accounting firm size has a negative effect on audit delay. The implication of this research is that the company should pay more attention and identify the factors that affect the audit delay. Mainwhile for mining companies it is to always maintain the level of profitability, solvency and use the services of the big four KAP so that they are encouraged to submit financial reports in a timely manner.